2000
DOI: 10.1023/a:1007673123716
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Although non-insulin-dependent diabetes mellitus (NIDDM) is considered a major cause of death, the role of some independent risk factors in diabetic patients is under debate. In fact the prognosis of NIDDM diabetes varies considerably in relation to the individual risk pattern, and the different studies are not directly comparable because of differences in size, age and geography of the samples, and type of statistical analysis. The aim of the study is to identify the independent predictors of mortality in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 67 publications
0
2
0
1
Order By: Relevance
“…Patients who have both HTN and diabetes mellitus are at a higher risk of experiencing cardiovascular events compared to nondiabetic HTN patients [ 21 ]. We found that diabetic patients with HTN demonstrated remarkably poor BP control ( P =0.010).…”
Section: Discussionmentioning
confidence: 99%
“…Patients who have both HTN and diabetes mellitus are at a higher risk of experiencing cardiovascular events compared to nondiabetic HTN patients [ 21 ]. We found that diabetic patients with HTN demonstrated remarkably poor BP control ( P =0.010).…”
Section: Discussionmentioning
confidence: 99%
“…While there is no doubt that diabetes harbors a causal effect on CVD [34-38] and all-cause mortality [36,39,40], whether these effects are exerted through hyperglycemia or whether it is just an innocent bystander has been increasingly challenged [41-43]. Overt diabetes has been shown to modify the effect on mortality of hyperglycemia [44].…”
Section: Discussionmentioning
confidence: 99%
“…В 6-летнем исследовании, проведенном в Италии и включавшем 683 пациента с СД 2, микро-и макроальбуми нурия оказались независимыми факторами риска сердеч но-сосудистой летальности. ЭАМ в диапазоне микро-или макроальбуминурии повышала относительный риск кардиоваскулярной смерти в 2 и 3 раза соответственно [14]. Дру гое проспективное исследование (п=939).…”
unclassified